EFL Students' Speaking Anxiety and Strategies in Indonesian Peer Interaction - Rhizma Rhizma; Aridah Aridah; Istanti Hermagustiana (Yayasan Visi Intan Permata, 2026)
This study examines the speaking anxiety experienced by EFL students when interacting in English with their Indonesian peers, as well as the strategies they use to alleviate it. This study employed a qualitative descriptive design involving semi-structured interviews with six Indonesian EFL undergraduates. Data were analysed using thematic analysis. The findings revealed four main factors causing anxiety: fear of negative evaluation from peers (including the proximity paradox, whereby students are actually more anxious around close friends), situational speaking pressure, linguistic insecurity, and internal psychological pressure (including professional identity threat). To manage their anxiety, students employed strategies such as independent practice (including self-recording and ChatGPT), emotional regulation, cognitive reframing of mistakes, and mindful communication (code-switching and language simplification). However, no participant reported that their anxiety had disappeared entirely. This study provides qualitative insight that enhances our understanding of foreign language anxiety in the context of peer interaction. It also offers practical recommendations for developing a more supportive environment for EFL speaking in Indonesian universities.